Verification of the CNOSSOS traffic noise prediction model – a case study - Pyffel, Remigiusz; Buszkiewicz, Maciej; Gołębiewski, Roman (Archives of Acoustics, 2026)
Pursuant to Commission Directive (EU) 2015/996 of 19 May 2015, which establishes common methods for noise assessment under Directive 2002/49/EC of the European Parliament and of the Council, EU Member States have been required to use the CNOSSOS method for noise mapping since the beginning of 2019. Consequently, from that year, the standardised CNOSSOS noise prediction method has been used to assess noise generated by moving vehicles. This method introduced a specific vehicle classification that differs from the classification proposed in the traffic noise prediction method recommended until 2019, i.e. the French NMPB-Routes-96 method. This paper compares the relationships between sound power level as a function of vehicle velocity according to the classifications adopted in the two traffic noise prediction methods. In addition, using the determined corrections to the sound power level, the CNOSSOS noise prediction method is verified by comparing measured and calculated equivalent sound levels.